Changing views on growth: What became of pro-poor growth? - Michael Grimm; Kacana Sipangule; Rainer Thiele; Manfred Wiebelt (Kiel Institute for the World Economy (IfW), Poverty Reduction, Equity and Growth Network (PEGNet), 2015)
Pro-poor growth is a promising development concept that links economic growth and poverty reduction ...and is still an integrated part of recent concepts like inclusive growth and shared prosperity...but faces the danger of losing priority in the extended list of goals and targets of the SDGs.
Keywords: 330